Advances in the study of nervous system infections in COVID‐19. Issue 3 (September 2021) - He, Chao; He, Ling; Chen, Lin; Wang, Wei
Shortly after its outbreak, coronavirus disease 2019 (COVID‐19) has very rapidly spread to become a global epidemic. Early clinical findings mainly included typical symptoms such as fever and cough with a very high transmission rate. Recent findings have demonstrated neurological manifestations of atypical symptoms, which is associated with poor prognosis. In this paper, we describe the neurological aspects of COVID‐19 pneumonia in terms of relevant neurons, virus‐associated receptors, and olfactory and neurological clinical manifestations and offer insights on treatment.